Ultrasound evaluation of fetal lung maturity, is it reliable? - Huamán Guerrero, Moisés (2016)
The purpose of this communication is to review the importance of fetal maturity determination by non-invasive procedures using ultrasound Doppler velocimetry and grayscale. The authors emphasize the importance of precisely specifying fetal lung maturity when deciding to terminate pregnancy for various indications in order to avoid consequences of prematurity including newborn’s respiratory distress syndrome (RDS) due to absence of lung surfactant that could lead even to death. The authors coincide that a multiparameter diagnosis of gestational age calculation starts from a first ultrasound study between 5 and 10 weeks, assessment of lung vascular impedance by Doppler accompanied by intestinal maturity, degree of cerebral corticalization, presence of nuclei ossification, current biometric fetal age and estimation of weight. They conclude emphasizing that in doubt and presence of a healthy fetus, with good growth, and normal hemodynamic biophysical profile, the more sensible course is to wait for the completion of gestation according to new criteria that redefine the duration of pregnancy and has been proposed by the ACOG.